The Influence Of Cutting Parameter On Heat Generation In High-Speed Milling Inconel 718 Under MQL Condition - Kasim, Mohd Shahir; Raja Abdullah, Raja Izamshah; Md Ali, Mohd Amran; Abdul Aziz, Mohd Sanusi; Mohd Abid, Mohd Asyadi 'Azam; Che Haron, Che Hassan; A Ghani, Jaharah (CSIR, 2014)
The paper presents a studyof the effect of operating variable parameter; cutting speed, feed rate, depth of cut and width of cut on heat being generated when end milling under MQL condition. The response surface methodology (RSM) was employed in the experiment, and a Box–Behnken design was used to determine the cause and effect of the relationship between the input variables and response. The investigated milling parameters were cutting speed (100 - 140 m/min), feed rate (0.1 - 0.2 mm/tooth), depth of cut (0.5-1.0 mm) and width of cut (0.2 -1.8 mm). Result of this study show ball nose end milling generates low temperature ranging from 69°C to 359°C. Experimental data and statistical analysis showed that heat generation was dominated by radial depth of cut, followed by axial depth of cut. Feed rate and cutting speed were found statistically not significant. The linear models were developed with a 92% confidence level. The optimum condition required for minimum heat generated include cutting speed of 117 m/min, feed rate of 0.11 mm/rev, axial depth of cut of 0.57 mm, and radial depth of cut of 0.21 mm. With this optimum condition, a minimum heat generated of 68°C was obtained.